2007
DOI: 10.1177/0047287506304049
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Cognitive and Affective Image in Predicting Choice Across Natural, Developed, and Theme-Park Destinations

Abstract: This study examines the role of cognitive and affective destination-image components in the formation of destination preferences from a multialternative/multiattribute perspective. In addition, the study examines the stability of those roles across three types of destinations. A total of 1,020 Taichung residents in Taiwan were administered an on-site questionnaire. The results indicated that cognitive and affective components of overall destination image influence tourists' destination preferences and that cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
174
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(188 citation statements)
references
References 47 publications
10
174
1
3
Order By: Relevance
“…Specifically, a tourist's pre-trip interest moves from the impersonal scenery and destination related touristic activities to the personal enjoyment and delights they anticipate for themselves and their intimates (Dann, 1993). Consequently, the recognition of conative image as an antecedent of the intention to revisit a destination reintroduces the need to examine conative images, which contradicts the suggestions of previous researchers who considered that the intent or action component of image is analogous to behavior (Çakmak & Isaac, 2012;Gartner, 1996;Hallmann et al 2014;Lee, 2009;Nadeau et al, 2008;Prebensen, 2007;Roth & Diamantopoulos, 2009;Stylidis, Belhassen, & Shani, 2014;White, 2005;Zhang et al 2014) or who disregarded conative image when examining images (Assaker 2014;Bigné, Sánchez & Sanz, 2009;Byon & Zhang, 2010;Hudson et al, 2011;Lam & Hsu, 2006;Lin, Morais, Kerstetter, & Hou, 2007;Ryan & Cave, 2005;San Martin & Rodríguez del Bosque, 2008).…”
Section: Theoretical Implicationsmentioning
confidence: 93%
“…Specifically, a tourist's pre-trip interest moves from the impersonal scenery and destination related touristic activities to the personal enjoyment and delights they anticipate for themselves and their intimates (Dann, 1993). Consequently, the recognition of conative image as an antecedent of the intention to revisit a destination reintroduces the need to examine conative images, which contradicts the suggestions of previous researchers who considered that the intent or action component of image is analogous to behavior (Çakmak & Isaac, 2012;Gartner, 1996;Hallmann et al 2014;Lee, 2009;Nadeau et al, 2008;Prebensen, 2007;Roth & Diamantopoulos, 2009;Stylidis, Belhassen, & Shani, 2014;White, 2005;Zhang et al 2014) or who disregarded conative image when examining images (Assaker 2014;Bigné, Sánchez & Sanz, 2009;Byon & Zhang, 2010;Hudson et al, 2011;Lam & Hsu, 2006;Lin, Morais, Kerstetter, & Hou, 2007;Ryan & Cave, 2005;San Martin & Rodríguez del Bosque, 2008).…”
Section: Theoretical Implicationsmentioning
confidence: 93%
“…Second, the variables related to the tourism supply chain were measured, such as airline companies, tour operators, travel agencies, and lodging companies [11,71]. Third, the complementary offer of the destination was measured, evaluating sports [72][73][74], leisure [75], shopping centers [76], and theme parks [77,78]. Fourth, the cultural offer has to do with the museums, history, and culture of the population of the tourism destination [79][80][81].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have consistently suggested that psychological benefits of green brands consisted of the following three sub-dimensions: (1) warm glow; (2) self-expressive benefits; and (3) nature experiences [20][21][22]. For instance, Hartmann and Apaolaza-Ibáñez [11] tested the uni-dimensionality of the three sub-dimensions using 432 samples and showed that there is no problem with convergent validity, discriminant validity, or internal consistency in the three sub-dimensions of psychological benefits of green brands.…”
Section: Psychological Benefits Of Green Brandsmentioning
confidence: 99%